2017
DOI: 10.15244/pjoes/66714
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Accumulation and Speciation of PM2.5 and Relevant Health Risk Assessment in Jinan, China

Abstract: Arsenic is a ubiquitous carcinogen and mutagen that has created serious human health problems around the world. It is released into the environment from both anthropogenic and natural sources [1]. Many studies have demonstrated anthropogenic sources such as the combustion of fuels, and the use of pesticides contributes As at three times higher levels than natural ones [2]. As toxicity and migration are significantly correlated with its speciation and oxidation state in the environment. In general, inorganic As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Pollutant concentration is one of the important factors affecting health risk assessment results (38)(39)(40). High levels of PM 2.5 exposure will increase the risk of some health endpoints such as respiratory, cardiovascular and lung diseases (41)(42)(43).…”
Section: Results and Discussion Pm 25 Concentration Status Reportmentioning
confidence: 99%
“…Pollutant concentration is one of the important factors affecting health risk assessment results (38)(39)(40). High levels of PM 2.5 exposure will increase the risk of some health endpoints such as respiratory, cardiovascular and lung diseases (41)(42)(43).…”
Section: Results and Discussion Pm 25 Concentration Status Reportmentioning
confidence: 99%
“…The correlations suggest that PM1-bound As comes from combustion emission (probably municipal emission-heating with use coal) and As compounds from combustion influence not only amounts of soluble As(V) in the ambient air but also its share in total PM1-bound As. As from combustion process is emitted mainly as arsenic trioxide, and prevailing oxidative As forms in PM are explained by oxidation of trivalent forms by oxidants such as ozone [27,28]. Seasonal changes in PM2.5-bound As(III) and As(V) had been noticed in research conducted in Jinan city situated in Shandong Province of China (area under the influence of coal combustion emissions, especially in winter).…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal changes in PM2.5-bound As(III) and As(V) had been noticed in research conducted in Jinan city situated in Shandong Province of China (area under the influence of coal combustion emissions, especially in winter). Analysis of As species in PM showed that only in some winter samples of PM2.5, As(III) was determined; the rest of As was present as As(V) [27].…”
Section: Resultsmentioning
confidence: 99%
“…The final simulated output is the sum of the estimated output and the estimated output error. The structure of the PEK approximator [31][32][33][34][35][36][37][38][39][40] is shown in Fig. 2, where n1, n2, …, nc denote the number of candidate input variables for Class 1, 2, …, nc, respectively; weight 1, weight 2, …, weight n denote combination weights for component networks; O(s), O(e), and E(e) denote simulated output, estimated output, and estimated output error, respectively.…”
Section: Pek-based Machine Learning Methodsmentioning
confidence: 99%